Consumer Interpretation of Green Marketing Campaigns: A Qualitative Study in the West Java Tourism Industry - Zulki Zulkifli Noor (Dinasti Publisher, 2025)
This study aims to explore marketing strategies based on digitalization, storytelling, and local wisdom implemented by MSMEs in West Java to increase competitiveness. With a qualitative approach and exploratory design, data were collected through in-depth interviews with MSME actors from the culinary, handicraft, and traditional clothing sectors. The findings show that digitalization of marketing through social media, such as Instagram and TikTok, helps MSMEs expand their market reach. However, low digital literacy is still a major obstacle. Storytelling is used to create emotional connections with consumers, especially through authentic narratives about the cultural and historical values ??of the product. The obstacle in storytelling lies in the consistency of story delivery. Local wisdom, such as traditional motifs or local materials, gives a unique identity to a product, but MSME actors often face a dilemma between maintaining cultural authenticity and following modern trends. This study confirms that the integration of digitalization, storytelling, and local wisdom can significantly increase the competitiveness of MSMEs. However, its success requires support in the form of digital literacy training, development of storytelling skills, and policies that support cultural preservation. This research is expected to provide practical contributions for MSME actors as well as recommendations for policy makers to support business sustainability in the digital era.